Small bowel angioectasia as a marker of frailty and poor prognosis - Robertson, Alexander R. (Endosc Int Open, 2020)
Background and study aims  This study aimed to establish 5-year survival of patients diagnosed with bleeding small bowel (SB) angioectasia, with the hypothesis that many will suffer deaths relating to comorbidity rather than gastrointestinaI bleeding. Patients and methods  SB capsule endoscopy (SBCE) procedures, performed for suspected SB bleeding or iron deficiency anemia, with angioectasia isolated as the cause of SB bleeding and at least 5 years of follow-up data were isolated (n = 125) along with an age-matched group with “normal” SBCE procedures (n = 125). These were retrospectively analysed with further information on mortality and comorbidity gathered through hospital records. Results  Those with angioectasia had a median age of 72.7 years and comorbidities were common. The 5-year survival was 64.0 % (80/125) compared to 70.4 % (88/125) in those with “normal” SBCE. Those with significant cardiac or vascular comorbidity had a poorer survival (52.9 % (37/70) at 5 years) but anticoagulation/antiplatelets/ number of lesions or requirement endoscopic treatment seemed to make little difference. In those with SB bleeding secondary to angioectasia none of the subsequent deaths were directly attributable to gastrointestinal bleeding. Conclusions  In this cohort, SB angioectasia did not lead to any deaths but the 5-year survival was poor due to those diagnosed often being older and having comorbidities. This would support the hypothesis that a diagnosis of SB bleeding secondary to angioectasia suggests frailty.